Development of Peer-Based Interaction Skills Assessment Instruments in Mathematics Learning Process in Class - Indah Nuraena; Budi Manfaat; Arif Muchyidin (MASI Mandiri Edukasi, 2022)
Interaction skills between students are needed during the learning process. If a student does not interact with the teacher or between students during the learning process in the classroom, they will have difficulty achieving maximum learning success. The purpose of this research and development is to develop an instrument for assessing interaction skills among students in the mathematics learning process in the classroom. This development method was adapted from the steps developed by Saefuddin Azwar, which started with the identification of measurement objectives, operationalization of aspects, item writing, language testing, field tests, item selection, and final compilation. The subject of the experiment was carried out on class VIII-C students of SMPN 3 Luragung. Based on the results of research and development at SMPN 3 Luragung to produce a peer-based interaction skill assessment product during the mathematics learning process in class, the researcher can conclude that the assessment of interaction skills between students can objectively assess interaction skills between students when learning mathematics so that the results of the assessment are more accurate. In addition, the validity and reliability of the test results of the instrument for assessing interaction skills between students in the learning process of mathematics in the classroom that has been developed indicate that this instrument is suitable for use in learning mathematics. With minimum validity of 1 of three authors, the reliability of the instrument is said to be very high, with a result of 0.91, and the item discrimination power is greater than the item-total correlation coefficient of 0.2